Testing for Structural Change in Panel Data: Application to a Study of U.S. Foreign Trade in Manufacturing Goods - Han, Aaron K.; Park, Daekeun (The Review of Economics and Statistics, 1989)
Aaron K. Han, Daekeun Park, Testing for Structural Change in Panel Data: Application to a Study of U.S. Foreign Trade in Manufacturing Goods, The Review of Economics and Statistics, Vol. 71, No. 1 (Feb., 1989), pp. 135-142